Comparison of Life Skills in Late Adolescents Majoring in Science and Social Studies - Manoe, Lafelia Mertanzha; Anakaka, Dian Lestari; Mage, Mernon Yerlinda Carlista; Littik, Serlie K. A (Universitas Nusa Cendana, 2024)
Adolescence is a transitional period from children to adults. Adolescents must be able to make decisions, think critically, evaluate themselves, have self-identity, and be close to their creator. All of these things are included in life skills. Life skills are the ability of a person to survive and live. For this reason, life skills are essential for everyone who strives to have a better life. This study aims to determine whether there are differences in life skills in science and social studies majors, with a sample of 204 participants. The method used in this study is quantitative research with comparative analysis and using questionnaire distribution. The results showed that the hypothesis test found that the significance value was 0.67 > 0.05, which indicates no significant difference in the life skills of science and social studies majors. It was also found that the science department is superior in interpersonal communication, problem-solving, and identity development. Meanwhile, the social studies department excels in the interpersonal dimension of physical fitness. Science majors get the highest points for problem-solving, and social studies majors have the highest points for identity development.